Examining Scaffolding Process in One-to-One Piano Lessons for Young Beginners: An Observational Analysis - Wong, Yiing Siing; Wang, I Ta; Hashim, Mohd Nasir (Malaysian Journal of Music, 2023)
In piano education, the initial stages of teaching young beginners establish the foundation for future endeavours. Due to the necessity of collaborative effort, piano lessons can be a complex process for both the teacher and the student. A balance must be found whereby the teachers can administer information in a way that is compatible with the student’s learning style. Therefore, the teacher must adapt their instruction to the level of the student. This exploratory case study investigates how scaffolding process is adapted into piano education in private setting to enhance the learning process of young beginner students. 10 teacher-student dyads, with students ages between 5-7 years, were recruited. Weekly lessons over a span of four weeks were observed and documented. Interviews with participants were conducted to find out more insights on their perspectives of teaching. Video data analysis was conducted based on the three characteristics–contingency, fading of support and transfer of responsibility–from the conceptual model of scaffolding. The findings indicate that two types of scaffolding process were applied in piano lessons–consistent and contingent, with the latter prevailing in most of the lessons. It was also observed that the three characteristics of scaffolding emerges within the same lesson and across several lessons, influenced by students’ readiness and response. Whilst there were differences among the contingency strategies used, certain tendencies recured across the teachers. Among these, modelling stood out as the as the predominant strategy and that teachers rely primarily on their perspectives and intuition when it comes to scaffolding.